Phase modification and magnetic energy product enhancement of PrCo5-based nanomaterials due to carbon addition. (January 2020) - Chang, H.W.; Wang, H.Y.; Lee, Y.I.; Guo, Y.M.; Chang, W.C.; Shaw, C.C.
Abstract: The magnetic properties, phase evolution, microstructure, and magnetic domain structure of melt-spun PrCo5- x C x and PrCo5 C y ( x = 0–0.4 and y = 0–0.4) flakes are compared. Binary PrCo5 flakes exhibit low intrinsic coercivity (i Hc ) of 3.2 kOe and thus a low magnetic energy product (( BH )max ) of 4.4 MGOe, which is attributed to the coarse grains. By doping with proper amounts of C, the well-modified phase composition and uniformly refined microstructure and magnetic domains enhance the magnetic properties remarkably. Different phase compositions found for two approaches for doping PrCo5 with C dominate the magnetic properties in addition to the fine microstructure. In PrCo5- x C x ( x = 0–0.4) flakes, the 2:17 phase suppressed by doping with C contributes to coercivity increase, and the largest i Hc of 13.5 kOe with ( BH )max = 8.8 MGOe is obtained for PrCo4.9 C0.1 flakes. For higher x, the formation of the 5:19 phase slightly reduces i Hc to 7.2–8.8 kOe and ( BH )max to 7.2–8.0 MGOe. In contrast, in the PrCo5 C y ( y = 0–0.4) series flakes, the increased amount of the 2:17 phase and the strengthened exchange coupling effect resulting from the refined microstructure caused by doping with a proper amount of C result in large ( BH )max of 11.8 MGOe with i Hc of 5.0 kOe for PrCo5 C0.3 flakes. Highlights: C doping significantly improves the magnetic properties of melt-spun PrCo5 flakes. C doping refines the sizes of the grains and magnetic domains. Different phase compositions for two approaches for C doping dominate the magnetic properties. In PrCo5- x C x, the suppressed 2:17 phase resulting from doping with C contributes to high intrinsic coercivity. In PrCo5 C y flakes, the 2:17 phase well coupled with the 1:5 phase results in high ( BH )max .